The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/13880209.2015.1120320
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD phenolic profile, cytotoxic and anti-kinetoplastidae activity ofMelissa officinalis

Abstract: Context Melissa officinalis subsp. inodora Bornm. (Lamiaceae) has been used since ancient times in folk medicine against various diseases, but it has not been investigated against protozoa. Objective To evaluate the activities of M. officinalis against Leishmania braziliensis, Leishmania infantum and Trypanosoma cruzi as well as its cytotoxicity in fibroblast cell line. Materials and methods The fresh leaves were chopped into 1 cm 2 pieces, washed and macerated with 99.9% of ethanol for 72 h at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Amongst phenolic acids, the most prevalent was caffeic acid with 6.42%, followed by ellagic (4.85%) and gallic acid (3.76%). In this study, rosmarinic acid was only a minor compound (2.2%) [ 32 ]. Another study reported sinapic and ferulic acid along with rosmarinic acid as main compounds [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amongst phenolic acids, the most prevalent was caffeic acid with 6.42%, followed by ellagic (4.85%) and gallic acid (3.76%). In this study, rosmarinic acid was only a minor compound (2.2%) [ 32 ]. Another study reported sinapic and ferulic acid along with rosmarinic acid as main compounds [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…MO is known for containing RA as its main compound, along with other phenolic compounds including ferulic acid, gallic acid, chlorogenic acid, syringic acid, p-coumaric acid, and caffeic acid, which are present in high proportions [60]. Caffeic acid, in particular, is found as another prominent phenolic in MO [61,62] and is more effective in inhibiting lipid oxidation and oil-in-water emulsion oxidation activities than RA [63]. Phenolic compounds as well as flavonoids are important active compounds of MO, although their profiles vary depending on the variety.…”
Section: Estimation Of Total Phenolics Content Rosmarinic Acid Conten...mentioning
confidence: 99%
“…For example, Echem and Chukwuike [22] demonstrated the availability of Melissa officinalis extracts for inhibiting the corrosion of aluminium in hydrochloric acid medium. In another work Cunha et al [25] analyzed the efficacy of these extracts against Leishmania and Trypanosoma activity, focusing on biomedical applications. Therefore, in this work a base WBPUU dispersion was synthesized and incorporated with aqueous extracts of Salvia officinalis L. and Melissa officinalis L. having in view the obtainment of products with improved antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%